2020
DOI: 10.2147/phmt.s260788
|View full text |Cite
|
Sign up to set email alerts
|

<p>Risk Factors of Perinatal Asphyxia Among Newborns Delivered at Public Hospitals in Addis Ababa, Ethiopia: Case–Control Study</p>

Abstract: Background: Perinatal asphyxia determines the newborn's future health status and viability with risk factors yet to be completely understood. It measures the status of the healthcare delivery of an organization including antenatal, intranatal, and postnatal care. In Ethiopia, 31.6% of neonatal mortality was attributed to perinatal asphyxia. This study aimed to assess the risk factors of perinatal asphyxia. Methods: An unmatched case-control study was conducted on 213 (71 cases selected using lottery method and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
17
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 23 publications
15
17
3
2
Order By: Relevance
“…Less than or equals to two ANC follow up by the mothers were 4.6 times higher odds of developing asphyxiated newborns than mothers who have more than four ANC follow up. This nding was inconsistent with the study conducted in Ethiopia [13,23,25]. This difference may be due to the number of health facilities included in the study and study period.…”
Section: Determinants Of Birth Asphyxia Among Newbornscontrasting
confidence: 74%
See 2 more Smart Citations
“…Less than or equals to two ANC follow up by the mothers were 4.6 times higher odds of developing asphyxiated newborns than mothers who have more than four ANC follow up. This nding was inconsistent with the study conducted in Ethiopia [13,23,25]. This difference may be due to the number of health facilities included in the study and study period.…”
Section: Determinants Of Birth Asphyxia Among Newbornscontrasting
confidence: 74%
“…Mal-presentation of foetus is associated with premature rupture of membrane; this premature rupture of membrane could leads to umbilical cord accidents occur with sub sequent asphyxia at birth [14]. But, the nding was inconsistent with previous studies conducted in Ethiopia [13,23]. This difference might be due to the difference in the study population and the study design.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…According to the reports of different studies conducted in Ethiopia, it was shown that the prevalence of perinatal asphyxia ranges from 12.5% to 32.8% [20,21]. Different findings in different countries show that primiparity, complications during pregnancy like preeclampsia/eclampsia and antepartum hemorrhage (APH), intrapartum complication like fever, cord around fetal neck, umbilical cord prolapse, malpresentation, prolonged labor, prolonged rupture of membranes (PROM) and administration of uterotonic drugs, prematurity, low birth weight (LBW), maternal age, and medical complication were identified as risk factors of perinatal asphyxia [20][21][22][23][24][25][26][27][28][29][30][31][32][33], while a retrospective study done in Ghana shows that the use of partographs during labor was associated with a reduced incidence of birth asphyxia [31]. Despite Ethiopia's remarkable success in achieving the MDG-4 goals before five years, the decrement in NMR was comparatively low after that success and at the end of the MDG era, the government of Ethiopia is again running to address the SDGs to decrease NMR by 2030 to at least 12/1000 live births [12,18,19,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Birth trauma is damage that occurs as a result of physical pressure during the birthing process, usually during transit through the birth canal. 39 …”
Section: Methodsmentioning
confidence: 99%